Visualization OD matrices using Geographical Information System (GIS) / Nuraida Sanin - Sanin, Nuraida (2006)
Knowledge of origin destination (OD) travel information is necessary for a wide range of transportation planning activities. The high labor cost and other expenses associated with conventional survey techniques for estimating OD trip-tables have motivated the development of models that can inexpensively estimate these flows from easily available traffic link volumes. The main purpose of this report is to carry out of the investigation in the feasibility study on visualization Origin-Destination (O-D) matrix using the Geographical Information Systems (GIS) for Seberang Perai Utara, Pulau Pinang. The OD matrices that obtained from manual calculation will show the OD desire straight line map by using GIS. Besides it, the development of OD database brought the flexibility in the phase of data analysis. Through this research, the visualization OD matrices using GIS will become the important tools in transportation planning.